Walka o przywództwo w gospodarce światowej między państwami a korporacjami transnarodowymi - Jankowiak, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
There are five main subjects creating the world economy. Two of them are: international companies (known also as Transnational Corporations - TNC) and national economies with the institution of a government. At the beginning years of the existence of the world's economy, the most important players were countries, but right now the dominant position shifted to Transnational Coiporation. Mentioned roles change is the consequence of the globalization process and internationalization of the national companies activities. This article presents the Wprost's magazine ranking comparing the potential of countries and TNC and author's own thoughts. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 149-158